Is an Intermediate Dose of LMWH Effective for Secondary Prevention of Recurrent Venous Thromboembolism in Pregnant Patients Diagnosed with Deep Vein Thrombosis or Pulmonary Embolism? Design of a Pilot Study - Gandara, Esteban (Université d'Ottawa / University of Ottawa, 2012)
Statement of the problem The primary objective of this thesis was to determine the best study design to evaluate the safety and effectiveness of an intermediate dose of low molecular weight heparin for secondary prevention of pregnancy associated VTE (PAVTE). An RCT was deemed unfeasible,so the use of a single arm study with prior evaluation of feasibility with a pilot study is proposed. // Methods - A systematic review was conducted to evaluate the efficacy of current strategies used for secondary prevention of PAVTE.A survey was used to elicit the non-inferiority margin. // Results - The pooled proportion of recurrent VTE in patients treated with full dose LMWH was 0.012(95% CI 0.006 to 0.02) and the rate of major bleeding was 0.025(95% CI=0.01 to 0.041). The non-inferiority margin was elicited at 2.5%. // Conclusions - Although a randomized controlled trial should be conducted whenever possible, in certain scenarios they are unfeasible. Therefore, an alternative study design should perhaps be used to evaluate the safety and efficacy of therapeutic strategies.
Keywords: Venous thormboembolism; pregnancy; Heparin; Low molecular weight heparin